Meaning of punakawan symbolic in guidance and counseling - Galang Surya Gumilang (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
This article describes and discusses about (1) Punakawan's Symbolic Meaning in Guidance and Counseling, (2) Analysis of symbolic meaning of Punakawan in Guidance and Counseling. Punakawan consists of four (4) personnel namely Semar, Gareng, Petruk and Bagong. In the world of puppetry, Punakawan is known as the nanny satria Pandawa 5 who devoted himself to nurture and become a servant of punakawan. In guidance and counseling, the term servant is equal to a counselor as a helper who helps sincerely to the counselee. That is, Punakawan and Counselor position and position together as a helper to help and memandirikan optimally so that problems from Pandavas / counselees can be resolved properly